Beyond the workfare state : labour markets, equalities and human rights - Carpenter, Mick; Freda, Belinda; Speeden, Stuart (Policy, 2007)
Beyond the workfare state explores equality, discrimination and human rights in relation to employability and 'welfare-to-work' policies bringing together a wide and distinctive range of illustrative studies that gives voice to a variety of potentially marginalised groups.